Exploring the early-life causes and later-life consequences of migration through a longitudinal study on ageing - Alan Barrett; Irene Mosca (Institute for the Study of Labor (IZA), 2012)
Between 2009 and 2011, fieldwork was undertaken for the first wave of the Irish Longitudinal Study on Ageing (TILDA). Extension information was collected on about 8,500 people aged 50 and over and living in Ireland, covering topics such as economic circumstances and health. One of the features of Ireland's older population is the remarkably high proportion of returned migrants, that is, former emigrants who have returned to live in Ireland. According to the TILDA data over 20 per cent of Ireland's over 50s are returned migrants. This group represents a sub-population who is likely to have faced specific challenges over the life-course and who may now have specific circumstances and needs. The group also provides an opportunity to explore the impacts of migration through the generally under-utilised approach of comparing stayers and returners. In this paper, the authors report on work which has been undertaken on return migrants using the TILDA data. This work has revealed higher rates of childhood abuse victimhood among the returned migrants, higher rates of alcohol problems among some of them and higher rates of social isolation. The work can inform the design of social policy within Ireland. It can also add to the international literature on the impacts of migration over the life-course.
Keywords: J14; J15; 330; return migrants; older adults; social isolation; child abuse; alcoholism; Alte Menschen; Rückwanderung; Lebensverlauf; Soziale Isolation; Alkoholkonsum; Kinder; Sexuelle Belästigung; Irland